Mobile application for Calisthenics Workout Guide in 2D animation / Muhamad Azrin Azaman - Azaman, Muhamad Azrin (2015)
Mobile application for Calisthenics Workout Guide in 2D animation is the system that has been developed for user to learn calisthenics workout through mobile application. This project is an enhancement of current mobile application for calisthenics workout that is less effective for user to learn the calisthenics exercises. The problems for current mobile application for calisthenics workout are not built or designed in a good interface. The content for the current application such as exercises and guide for each exercise need to be clear and can be understood by user. The system consists of five basic calisthenics exercises which are push-up, pull-up, bench dips, sit-up and squat. This system applied system development methodology which is using ADDIE model. Since the system is in multimedia framework, this methodology is suitable thus it is fast and low-cost software development. ADDIE model consists of five phases but in this project development, developer only uses three phases due to time constraint. The phases are analysis, design and development. The system was fully develop using Adobe Flash Professional CC.